Lectin drug conjugate therapy for colorectal cancer. Issue 12 (2nd November 2020) - Kitaguchi, Daichi; Oda, Tatsuya; Enomoto, Tsuyoshi; Ohara, Yusuke; Owada, Yohei; Akashi, Yoshimasa; Furuta, Tomoaki; Yu, Yang; Kimura, Sota; Kuroda, Yukihito; Kurimori, Ko; Miyazaki, Yoshihiro; et al.
Abstract: Drug resistance represents an obstacle in colorectal cancer (CRC) treatment because of its association with poor prognosis. rBC2LCN is a lectin isolated from Burkholderia that binds cell surface glycans that have fucose moieties. Because fucosylation is enhanced in many types of cancers, this lectin could be an efficient drug carrier if CRC cells specifically present such glycans. Therefore, we examined the therapeutic efficacy and toxicity of lectin drug conjugate therapy in CRC mouse xenograft models. The affinity of rBC2LCN for human CRC cell lines HT‐29, LoVo, LS174T, and DLD‐1 was assessed in vitro. The cytocidal efficacy of a lectin drug conjugate, rBC2LCN‐38 kDa domain of pseudomonas exotoxin A (PE38) was evaluated by MTT assay. The therapeutic effects and toxicity for each CRC cell line‐derived mouse xenograft model were compared between the intervention and control groups. LS174T and DLD‐1 cell lines showed a strong affinity for rBC2LCN. In the xenograft model, the tumor volume in the rBC2LCN‐PE38 group was significantly reduced compared with that using control treatment alone. However, the HT‐29 cell line showed weak affinity and poor therapeutic efficacy. No significant toxicities or adverse responses were observed. In conclusion, we demonstrated that rBC2LCN lectin binds CRC cells and that rBC2LCN‐PE38 significantly suppresses tumor growth in vivo. In addition, the efficacy of the drug conjugate correlated with its binding affinity for each CRC cell line. These results suggest that lectin drug conjugate therapy has potential as a novel targeted therapy for CRC cell surface glycans. Abstract : rBC2LCN lectin showed affinity for colorectal cancer (CRC) cell surface. rBC2LCN‐PE38 suppressed subcutaneous CRC tumor growth rates in mouse models. Lectin drug conjugate therapy could be a novel therapeutic option for CRC.